Tannin: a new insight into a key product for the bioeconomy in forest regions. (21st April 2021) - Pagliaro, Mario; Albanese, Lorenzo; Scurria, Antonino; Zabini, Federica; Meneguzzo, Francesco; Ciriminna, Rosaria
Abstract: Produced by extraction from certain woods and barks with boiling water, tannin is the name given to a mixture of high molecular weight biophenols increasingly used in a number of industries. This study offers a new bioeconomy insight into an old natural product that, we argue in this study, will likely play a crucial role in the development of the bioeconomy of forest regions. After providing an updated picture of selected key economic and production aspects, we show how flourishing research on tannin's biological activity and technological applications has revealed many new properties that are likely to drive significant growth in demand in the near and mid‐term future. The study concludes with two lessons learned and one forecast that will hopefully accelerate progress in the bioeconomy of forest areas based on the circular economy of tannin enabled by new extraction and purification technologies. © 2021 Society of Industrial Chemistry and John Wiley & Sons Ltd.